Diet dan Aktivitas Fisik terhadap Hipertensi pada Masyarakat di Desa Lau Bakeri - Sri Febriani Marbun; Shahrul Rahman (Indo Publishing, 2025)
Hypertension, known as the silent killer, is a leading cause of global death. Diet and physical activity play a crucial role in controlling blood pressure. However, in rural areas like Lau Bekeri Village, information on the dietary habits and physical activity levels of elderly people with hypertension is limited. This study aims to identify dietary and physical activity patterns that can reduce hypertension rates in elderly people in Lau Bekeri Village, through direct community involvement and collaboration with local health workers. The method used was a descriptive approach with quantitative analysis, including health education and physical examinations of 15 elderly people in Lau Bekeri Village. The results showed that several elderly people suffered from hypertension, which can be identified through blood pressure and blood sugar checks. Through effective education on diet, physical activity, and the importance of regular health checks, public awareness of hypertension will increase. An education program involving elderly people and utilizing local media is expected to broaden information and encourage changes in elderly health behaviors. The results of this study contribute to hypertension prevention efforts in Lau Bekeri Village through a comprehensive and sustainable approach. A hypertension reduction program in the village needs to involve routine community activities, utilize local resources, support government policies, and provide ongoing evaluation.